2017
DOI: 10.1016/j.tet.2017.01.048
|View full text |Cite
|
Sign up to set email alerts
|

Copper-catalyzed [1,2]-rearrangements of allylic iodides and aryl α-diazoacetates

Abstract: The [1,2]- and [2,3]-rearrangements of iodonium ylides are synthetically useful reactions for the generation of functionalized α-iodoesters. Allylic iodides are coupled with α-diazoesters in the presence of a copper catalyst and a ligand to generate iodonium ylides, which undergo metal-mediated rearrangements. By fine-tuning the structure of the ligand, we have reversed the regioselectivity of copper-catalyzed reactions of iodonium ylides from [2,3]- to [1,2]-rearrangements with the use of alternate bipyridine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Based on experiments ,, and previous reports, , four possible pathways can be proposed for the catalytic [2,3]-sigmatropic rearrangements (Scheme ). After the nucleophilic addition of the allylic iodide/sulfide to the copper­(I)-carbene, Path-A experiences the electrophilic attack of metal-bound iodonium ylide; Path-B undergoes the electrophilic attack of free ylide; Path-C undertakes electrophilic attack after keto–enol tautomerism; and Path-D proceeds via sequential keto–enol tautomerism and electrophilic attack of free ylide.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Based on experiments ,, and previous reports, , four possible pathways can be proposed for the catalytic [2,3]-sigmatropic rearrangements (Scheme ). After the nucleophilic addition of the allylic iodide/sulfide to the copper­(I)-carbene, Path-A experiences the electrophilic attack of metal-bound iodonium ylide; Path-B undergoes the electrophilic attack of free ylide; Path-C undertakes electrophilic attack after keto–enol tautomerism; and Path-D proceeds via sequential keto–enol tautomerism and electrophilic attack of free ylide.…”
Section: Introductionmentioning
confidence: 94%
“…It was not until 1998 did Doyle et al develop the first enantioselective iodonium ylide rearrangement but with only moderate yields and low selectivities . Recently, Tambar and co-workers made outstanding contributions in the area of rearrangement reactions of iodonium ylides , and reported a highly stereoselective [2,3]-rearrangement of iodonium ylides by employing a chiral copper catalyst (Scheme , eq (1)) . This reaction represents the first highly enantioselective, diastereoselective, and regioselective [2,3]-rearrangement of substituted iodonium ylides, the products of which can be converted into a series of chiral building blocks including the ones that are inaccessible by classical onium ylide rearrangements.…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported the regioselective [2,3]- and [1,2]-rearrangements of iodonium ylides for the generation of racemic iodoester products. [8] Seminal studies by Doyle and co-workers reported that a single iodonium ylide substrate generated from unsubstituted allylic iodide underwent enantioselective rearrangement (69% ee), but there was no indication of the regioselectivity or diastereoselectivity. [9] To date, there are no catalytic rearrangements of these reactive substrates that can generate one product in high selectivity.…”
mentioning
confidence: 99%
“…We recently reported the regioselective [2,3]-and [1,2]-rearrangements of iodonium ylides for the generation of racemic iodoester products. [8] Seminal studies by Doyle and co-workers reported that as ingle iodonium ylide substrate generated from unsubstituted allylic iodide underwent enantioselective rearrangement (69 % ee), but there was no indication of either the regio-or diastereoselectivity. [9] To date,there are no catalytic rearrangements of these reactive substrates which can generate one product in high selectivity.H erein we describe the first highly enantioselective,d iastereoselective,a nd regioselective [2,3]-rearrangements of substituted iodonium Scheme 1.…”
mentioning
confidence: 99%